Serasi handmade cosmetic: brand awareness / Farina Aisya Daud - Daud, Farina Aisya (Faculty of Art and Design, 2020)
The cosmetics industries in Malaysia are very encouraging. However, many of the users are not aware of the products they are using on their faces.